The Roles of Family, Community, and Services in the Prevention of Illicit Drug Use: Findings From a Sample of Released Prisoners - Liu, Lin (Journal of drug issues, 2021)
Studies show that the deterioration of family bonds and financial difficulty are barriers to a successful reintegration after incarceration. However, how family, community, and correction agencies simultaneously affect individuals’ illicit drug use during reentry is rarely examined. This study draws insights from the systemic model of social disorganization and examines the joint effects of private, parochial, and public levels of social control on post-release drug use. We used a longitudinal data set that captured family relationships, community cohesiveness, and reentry program participation of released prisoners. Findings provide empirical support for the application of the systemic model of social disorganization on illicit drug during reentry. The various levels of social control defined by this theory were found to exhibit significant and inhibitory effects on individuals’ drug use after release. This study advances our understanding of individuals’ reentry outcomes by highlighting the joint influence of family, community, and correction agencies. Policy implications for addressing post-release drug use are presented.